The State of Secularism: Religion, Tradition and Democracy in South Africa - Leatt, Dhammamegha Annie ca. 20./21. Jh. (Witwatersrand University Press, 2017)
A history of global political secularism by comparing religion and traditional authority in apartheid South Africa with the post-apartheid state focussing on an analysis of tensions between secularity (in South Africa's Constitution and judicial foundations) and increasing non-secularity (in its embrace of traditional authorities and customary law).